Palgrave advances in the modern history of sexuality - Cocks, Harry; Houlbrook, Matt (Palgrave Macmillan, 2006)
Palgrave Advances in the Modern History of Sexuality offers a comprehensive and accessible overview of historical debate in the history of European and American sexuality since c. 1750. Each chapter explores in detail one theme, such as race, pornography, marriage, science or religion, which historians have seen as essential to writing the history of sexuality. The book therefore not only offers a broad introduction to the state of the art, but also suggests new directions for research and debate.